Personalized SC-IAT: A Possible Way of Reducing the Influence of Societal Views on Assessments of Implicit Attitude toward Smoking. Issue 1 (August 2014) - Bardin, Brigitte; Perrissol, Stéphane; Py, Jacques; Launay, Céline; Escoubès, Florian
The Implicit Association Test (IAT) is used to assess attitude beyond the limitations of explicit measurements. Nevertheless, the test requires opposition between two attitude objects and also measures an extra-personal dimension of attitude that may reflect associations shared collectively. The first limitation can be overcome by using a Single Category IAT and the second by a personalized version of IAT. This study compares attitudes to smoking measured using a Single Category IAT with a personalized version of the test. The results, collected from 111 students, showed that the Single Category IAT did not distinguish smokers from non-smokers; smokers had negative scores. The personalized version did distinguish smokers from non-smokers, and smokers' scores seem to be neutral.